2017
DOI: 10.15698/mic2017.04.567
|View full text |Cite
|
Sign up to set email alerts
|

Thiol trapping and metabolic redistribution of sulfur metabolites enable cells to overcome cysteine overload

Abstract: Cysteine is an essential requirement in living organisms. However, due to its reactive thiol side chain, elevated levels of intracellular cysteine can be toxic and therefore need to be rapidly eliminated from the cellular milieu. In mammals and many other organisms, excess cysteine is believed to be primarily eliminated by the cysteine dioxygenase dependent oxidative degradation of cysteine, followed by the removal of the oxidative products. However, other mechanisms of tackling excess cysteine are also likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(66 reference statements)
2
13
0
Order By: Relevance
“…The involvement of threonine biosynthesis during high levels of cysteine was also reported in Escherichia coli more than three decades ago—where it was suggested that cysteine inhibits homoserine dehydrogenase (Hom6 in yeast) (44), acetohydroxyacid synthetase (Ilv6 in yeast) (45), and threonine deaminase (Ilv1 in yeast) (46). Furthermore, cysteine increases the levels of arginine and the enzymes involved in its biosynthesis, and this observation is in agreement with a recent report, suggesting that high levels of cysteine increase arginine biosynthesis for polyamine synthesis (47).…”
Section: Discussionsupporting
confidence: 93%
“…The involvement of threonine biosynthesis during high levels of cysteine was also reported in Escherichia coli more than three decades ago—where it was suggested that cysteine inhibits homoserine dehydrogenase (Hom6 in yeast) (44), acetohydroxyacid synthetase (Ilv6 in yeast) (45), and threonine deaminase (Ilv1 in yeast) (46). Furthermore, cysteine increases the levels of arginine and the enzymes involved in its biosynthesis, and this observation is in agreement with a recent report, suggesting that high levels of cysteine increase arginine biosynthesis for polyamine synthesis (47).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, cysteine increases the levels of arginine and the enzymes involved in its biosynthesis, and this observation is in agreement with a recent report suggesting that high levels of cysteine increase arginine biosynthesis for polyamine synthesis 47 .…”
Section: Cysteine Inhibits Translation and Rewires Amino Acid Metabolismsupporting
confidence: 93%
“…The protocol for RNA isolation, labeling, hybridization, scanning was followed as described previously [ 21 ]. Microarray data was analyzed and submitted to the Gene Expression Omnibus (GEO) database (GSE10859).…”
Section: Methodsmentioning
confidence: 99%